Merck : pricing Gardasil - Calkins, Tim; Vora, Megha ([London] : SAGE, 2016)
Allison Watkins, senior director of Merck's Vaccines Division, needed to decide on the pricing of Gardasil, Merck's newest vaccine and one of the company's most important product launches of the year. The outside consulting firm she had hired to recommend a price for Gardasil had suggested a price of $120 per dose (or $360 per person, as each person required three doses over six months to achieve adequate immunity). The Gardasil marketing team disagreed about this recommended price; some thought it was clearly too high, whereas others said it was too low. This case examines how Merck resolved this issue.
Originally Published in: Calkins, T., & Vora, M. (2009). Merck: Pricing Gardasil. 5-308-505. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Merck & Co; Drugs -- Prices -- Case studies; Pricing -- Case studies